Migrasi desa ke bandar : suatu tinjauan ke atas pengalaman masyarakat kelabit di Bario - Kebing, Harris (Universiti Malaysia Sarawak, UNIMAS, 2001)
The Kelabit is a minority indigenous community in Sarawak inhabiting the highland in the eastern part of the Baram District, with Bario constituting the largest settlement. The primary aim of the study was to assess the impact of the out-migration amongst the Kelabit to the nonmigrants in Bario.